2019
DOI: 10.1093/jac/dkz474
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic appropriateness and guideline adherence in hospitalized children: results of a nationwide study

Abstract: Background Information on the nature and appropriateness of antibiotic prescribing for children in hospitals is important, but scarce. Objectives To analyse antimicrobial prescribing and appropriateness, and guideline adherence, in hospitalized children across Australia. Patients and methods We analysed data from the National Antimicrobial Prescribing Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…These data support identifying targets for action, and they are a core contributor to both patient safety 11 and AMR initiatives. 9,15,16 In this study, we provided a detailed Australia-wide snapshot of hematology and oncology patients, which allows in-depth evaluation of antimicrobial prescribing and utilization among these vulnerable patient groups. We identified a number of areas unique to hemBMT and to oncology suitable for stewardship intervention.…”
Section: Discussionmentioning
confidence: 99%
“…These data support identifying targets for action, and they are a core contributor to both patient safety 11 and AMR initiatives. 9,15,16 In this study, we provided a detailed Australia-wide snapshot of hematology and oncology patients, which allows in-depth evaluation of antimicrobial prescribing and utilization among these vulnerable patient groups. We identified a number of areas unique to hemBMT and to oncology suitable for stewardship intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a very variable level of adherence to existing guidelines has already been observed by the treating physicians for a wide range of pediatric diseases. For example, guideline adherence regarding the use of antibiotics in infectious disease is a highly investigated subject [ 19 , 20 , 21 ]. These studies showed no change of management in urinary tract infections after introduction of the guideline, whereas the use of antibiotics in community-acquired pneumonia was evidence-based.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a very variable level of adherence to existing guidelines has already been observed by the treating physicians for a wide range of paediatric diseases. Guideline adherence regarding the use of antibiotics in infectious disease is a highly investigated subject [15][16][17]. The studies showed no change of management in urinary tract infections after introduction of the guideline, whereas the use of antibiotics in CAP was evidence-based.…”
Section: Discussionmentioning
confidence: 99%